The Effect of Binahong (Anredera cordifolia (Ten.) Steenis) Medicinal Plant Extract Addition on Glucose Detection - Dennis Farina Nury; Tri Widjaja; Fredy Kurniawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2019)
The potential of binahong (Anredera cordifolia (Ten.) Steenis) medicinal plant extract as glucose biosensor have been analyzed using cyclic voltammetry (CV) method. Glucose biosensor was prepared by modified electropolymerization technique of polypyrrole (PPy) to the active materials, such as binahong (Anredera cordifolia (Ten.) Steenis on the surface of gold electrode. Modified pyrrole polymerization was conducted at potential -1.3 to +1.3 V using voltammetry method with sweep rate 50mV/s for 30 cycles at pH 6.8. The performance of the modified sensor was tested in samples: glucose, urea, ascorbic acid and uric acid at the same concentration 10 mM, respectively. All samples were analysed using cyclic voltammetry method from -1.3 to +1.3 V with sweep rate of 50 mV/s in 0.1 M phosphate buffer at neutral condition (pH 7) room temperature. The best response of polypyrrole-binahong (Anredera cordifolia (Ten.) Steenis)-modified gold electrode was obtained during glucose measurement. No response detected from urea, ascorbic acid and uric acid. The result was proved that the modified electrode has a good potential for selective electrochemical sensor in determination of glucose.